A Differential Immune Modulating Role of Vitamin D in Urinary Tract Infection. (3rd April 2022) - Pirdel, Leila; Pirdel, Manijeh
ABSTRACT: Vitamin D is known as an important modulator of numerous immune functions. We aimed to investigate the association of 25-hydroxyvitamin D [25(OH)D] with several humoral mediators of the immune system in the patients with urinary tract infection (UTI) caused by uropathogenic E. coli (UPEC). Serum levels of 25(OH)D, cytokines (interferon (IFN)-γ, interleukin (IL)–4, IL-6, IL–10, IL-17A, Tumor necrosis factor (TNF)–α, and transforming growth factor (TGF)–β, immunoglobulin (Ig) isotypes (IgG, IgM, and IgA), complement proteins (C3 and C4) with hemolytic activities (CH50 and AP50), and nitric oxide (NO) were evaluated in 65 patients, compared to 45 age- and sex-matched healthy controls. An insignificant decrease in 25(OH)D levels was observed in patients, compared to controls. In the patient group, elevated levels of IFN-γ, IL-17A, and IL-10 had a significant association with the serum levels of 25(OH)D, while the levels of TGF-β, IL-6, and TNF-α showed an insignificant association. The levels of IgG, C3, and NO also displayed such a statistically significant association with serum 25(OH)D levels. The AP50 levels which had significant difference were found to be not associated with serum 25(OH)D levels. Vitamin D might mediate a link between the innate and adaptive immune responses via the induction of Th1/Th17 polarization of cytokine responses and isotype regulation of antibody production, along with the maintenance of the capacity of the alternative complement pathway, in response to a UPEC infection. However, further studies are needed to validate the defined nature of the host immune response.